The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1124/mol.55.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Daunorubicin- and Mitoxantrone-Triggered Phosphatidylcholine Hydrolysis: Implication in Drug-Induced Ceramide Generation and Apoptosis

Abstract: Several studies have suggested that diacylglycerol can affect the induction of apoptosis induced by toxicants and ceramide. The present study demonstrates that clinically relevant concentrations of the chemotherapeutic drugs daunorubicin and mitoxantrone (0.2-1 M) transiently stimulated concurrently with sphingomyelin-derived ceramide generation and diacylglycerol and phosphorylcholine production within 4 to 10 min via phospholipase C hydrolysis of phosphatidylcholine. Pretreatment of cells with the xanthogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…This result suggests that DNR may trigger in parallel both cell death (CER) and survival (DAG and phosphorylcholine) mediators and that, in sensitive leukemic cells, CER overrides the protective function of DAG and phosphorylcholine. 91 These results support the notion that reciprocal regulation through DAG and CER may be implicated in the regulation of apoptosis. 92 The mechanism by which phosphatidylcholine-derived DAG influenced intracellular CER concentration in DNR-treated cells is not yet characterized; however, because phosphatidylcholinederived DAG did not appear to influence N-SMase stimulation, it is conceivable that DAG enhanced CER metabolism by facilitating sphingomyelin synthesis.…”
Section: Implication Of Phosphatidylcholine Metabolism In Dnr-inducedsupporting
confidence: 80%
“…This result suggests that DNR may trigger in parallel both cell death (CER) and survival (DAG and phosphorylcholine) mediators and that, in sensitive leukemic cells, CER overrides the protective function of DAG and phosphorylcholine. 91 These results support the notion that reciprocal regulation through DAG and CER may be implicated in the regulation of apoptosis. 92 The mechanism by which phosphatidylcholine-derived DAG influenced intracellular CER concentration in DNR-treated cells is not yet characterized; however, because phosphatidylcholinederived DAG did not appear to influence N-SMase stimulation, it is conceivable that DAG enhanced CER metabolism by facilitating sphingomyelin synthesis.…”
Section: Implication Of Phosphatidylcholine Metabolism In Dnr-inducedsupporting
confidence: 80%
“…DNR stimulated N-SMase activity with a maximum of 129 ± 177% increase within 4 ± 15 min in Ba/F3-wt and Ba/F3-Kit cells but not in Ba/F3-KitD27 and Ba/F3-Kit+SCF cells (Figure 3). These results showed that DNR triggered N-SMase activity in Ba/F3 cells with a similar magnitude and kinetics than previously documented in other leukemic cellular models (Allouche et al, 1997(Allouche et al, , 2000BettaõÈ eb et al, 1999;Coà me et al, 1999;Jare zou et al, 1996;Mansat et al, 1997a,b), and that Kit activation blocked DNRinduced SMase stimulation.…”
Section: Influence Of Kit Activation On Dnr-induced N-smase Stimulationsupporting
confidence: 86%
“…In further studies, we showed that, at least in some leukemic cellular models, DNR activates the sphingomyelin (SM)-ceramide (CER) cycle leading to apoptosis. Indeed, DNR stimulated neutral sphingomyelinase (N-SMase) activity responsible for SM hydrolysis and subsequent CER generation in leukemic cells (Allouche et al, 1997(Allouche et al, , 2000BettaõÈ eb et al, 1999;Coà me et al, 1999;Jare zou et al, 1996;Mansat et al, 1997a,b). The fact that cell-permeant CER as well as natural CER (generated by exposure of the cells to bacterial SMase) induce apoptosis in these cells strongly suggests that CER plays an important role in DNR-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several chemotherapeutic drugs were shown to activate a sphingomyelinase in leukemic cells, including daunorubicin, mitoxantrone, etoposide, vincristine, dexamethasone, ara-C and cis-platinum. [206][207][208][209] …”
Section: Lipid-dependent Signaling Pathwaysmentioning
confidence: 99%